MADRASAH HEAD'S STRATEGY IN IMPROVING THE COMPETITIVE ADVANTAGE OF EDUCATIONAL INSTITUTIONS - Chotimah, Chusnul; Salam, Afdus; Amin, Nurul; Miftahuddin, Miftahuddin (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
The development of the current digital era demands a change in management in the world of education. Madrasas are one of the Islamic educational institutions that are required to be able to adapt to the times and meet the needs of society. Educational institutions that are unable to adapt to the times will stagnate, and may even go out of business. This paper aims to obtain an overview of the principal's strategy in increasing the competitive advantage of educational institutions at Madrasah Aliyah Negeri 1 Pasuruan. By using descriptive qualitative methods through in-depth interviews, participant observation and documentation, which are then analyzed, this paper gets the results; (1) Competitive advantages targeted by madrasas are strategies for developing academic and non-academic curricula, developing human resources and implementing the ITS Productistic Excellence program; (2) The process of implementing the strategy in madrasas is carried out collaboratively, by describing the strategies that have been formulated in the form of activities that support the implementation of the determined strategy. As for the technical implementation, the institution cooperates with internal and external parties. This paper contributes to the fact that internal and external collaborative strategies for educational institutions are very urgent for improving the quality of education.